PENGARUH ASIMETRI INFORMASI, KONSENTRASI KEPEMILIKAN, MANAJEMEN LABA DAN PERTUMBUHAN ASET TERHADAP COST OF EQUITY CAPITAL PADA PERUSAHAAN PERKEBUNAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sutarman, Aman; Karamoy, Herman; Gamaliel, Hendrik (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2022)
This study aimed to examine the influence of asymmetric information, ownership concentration, earnings management, and asset growth on the cost of equity capital in plantation companies listed on the Indonesia Stock Exchange. This research was quantitative research using secondary data. A total of 23 companies engaged in the plantation sector were used as samples, while the total eligible data sample to be analyzed was 65 annual financial report data. The theories used as the reference related to the research variables were agency theory, signal theory, pecking order theory, and trade off theory. While the research method used to analyze the data in the study was the multiple linear regression method using SPSS program version 25. The results showed that the asymmetric information variable had an influence in increasing the cost of equity capital. The concentration of ownership, earnings management, and asset growth had no influence in increasing the cost of equity capital. However, the independent variables simultaneously were not able to influence the dependent variable.